Implementation of the Forest School Model to Improve Creativity and Problem Solving Skills of Junior High School Students - Firayani, Firayani (Scientica Education Journal, 2026)
This study aims to examine the application of the Forest School model in improving creativity and problem-solving skills in junior high school students. The background of the study is based on the limitations of conventional learning, which is not optimal in developing 21st-century skills, especially creativity and problem-solving abilities. The study used a qualitative approach with a case study design to gain an in-depth understanding of the process, experience, and meaning of nature-based learning. The research subjects included junior high school students, teachers, and school officials directly involved in the implementation of the Forest School model. Data collection was conducted through participant observation, in-depth interviews, and documentation, while data analysis used an interactive model that included data reduction, data presentation, and conclusion drawing. The results showed that the Forest School model was able to create authentic learning experiences through exploration of the natural environment that encouraged active student involvement. Student creativity developed through open-ended activities, divergent thinking, and the courage to experiment, while problem-solving skills were honed through real-life problems that required observation, decision-making, and reflection. The role of teachers as facilitators and a collaborative learning environment strengthened the effectiveness of learning. This study concluded that the Forest School model is an innovative, relevant learning approach and has the potential to improve the quality of junior high school students' learning process in a sustainable manner.